Epidemiological profile and molecular genetic characterization of HIV-1 among female sex workers and elderly male clients in Guangxi, China - Chen, Xiu (Emerg Microbes Infect, 2021)
The HIV/AIDS prevalence in female sex workers (FSWs) and elderly male clients is increasing in Guangxi, China, but the transmission relationship between them remains unclear. This study aims to illuminate the transmission network between FSWs and elderly male clients using molecular epidemiological analyses. Phylogenetic analysis indicated that CRF01_AE was the dominant strain, followed by CRF07_BC and CRF08_BC in both groups. Multivariate logistic regression analysis indicated that viral loads of 50 to 1000 copies/mL, immunological treatment failure and CRF07_BC were risk factors for entering the transmission network. Transmission network analysis showed that CRF07_BC tended to form large clusters, whereas CRF01_AE tended to form multiple but small clusters. Two groups of 11 FSWs and 169 clients were intricately intertwined. Spatial analysis demonstrated the formation of hotspots and clusters of transmission sharing regional differences. In conclusion, our study provides direct genetic evidence of transmission linkages between FSWs and elderly male clients. Although the CRF01_AE subtype was still the predominant subtype in the region, the higher degree and larger clusters found in CRF07_BC illustrate a rapid and intensive uptrend, which is expected to increase its prevalence in the region in the future.